Elevated O-GlcNAcylation induces an antidepressant-like phenotype and decreased inhibitory transmission in medial prefrontal cortex - Cho, Yoonjeong; Hwang, Hongik; Rahman, Md. Ataur; Chung, ChiHye; Rhim, Hyewhon (Nature Publishing Group, 2020)
Depression is a devastating mental disorder affected by multiple factors that can have genetic, environmental, or metabolic causes. Although previous studies have reported an association of dysregulated glucose metabolism with depression, its underlying mechanism remains elusive at the molecular level. A small percentage of glucose is converted into uridine diphosphate-N-acetylglucosamine (UDP-GlcNAc) via the hexosamine biosynthetic pathway, which serves as an immediate donor for protein O-GlcNAc modification. O-GlcNAcylation is a particularly common post-translational modification (PTM) in the brain, and the functional significance of O-GlcNAcylation in neurodegenerative diseases has been extensively reported. However, whether the degree of O-GlcNAc modification is associated with depressive disorder has not been examined. In this study, we show that increased O-GlcNAcylation levels reduce inhibitory synaptic transmission in the medial prefrontal cortex (mPFC), and that Oga(+/-) mice with chronically elevated O-GlcNAcylation levels exhibit an antidepressant-like phenotype. Moreover, we found that virus-mediated expression of OGA in the mPFC restored both antidepressant-like behavior and inhibitory synaptic transmission. Therefore, our results suggest that O-GlcNAc modification in the mPFC plays a significant role in regulating antidepressant-like behavior, highlighting that the modulation of O-GlcNAcylation levels in the brain may serve as a novel therapeutic candidate for antidepressants.